Effective handwriting recognition algorithm for biometric identification methods - Галла, Ю. В. (Problems of Informatization and Control, 2008)
The problem of improving the efficiency of the biometric identification of individuals, the principles of biometric identification systems. The described system of identification for unconscious dynamics of human movement, the principle of their functioning and effectiveness of the main problems that arise in their work. To improve the performance of such systems proposed parallel analysis of dynamic and static characteristics of the handwriting. The efficient pre-processing algorithms and image recognition. The estimate of the possibility of building on this principle